2022
DOI: 10.3390/ijerph19148625
|View full text |Cite
|
Sign up to set email alerts
|

Rationing Care, Job Satisfaction, Fatigue and the Level of Professional Burnout of Nurses in Urology Departments

Abstract: The problem of rationing nursing care is common and present all over the world, which is a direct threat to the health and life of patients. The aim of the study was to assess the level of rationing care, fatigue, job satisfaction and occupational burnout and to assess the relationship between them and age, length of service and the number of jobs. A survey was performed among 130 Polish nurses in urology departments using the following questionnaires: Link Burnout Questionnaire, Job Satisfaction Scale, Nursin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Although nurses reported a variety of nursing activities as not completed, the mean score showed that frequency of nursing care rationing was in the range from between 'never' and 'rarely'. The same range (less than rarely) of rationed nursing care frequency has also been found in several Polish studies (Jarosz et al, 2022;Kołtuniuk et al, 2021;Piotrowska et al, 2022;Witczak et al, 2022) or in Slovak study (Kalánková et al, 2022).…”
Section: Discussionsupporting
confidence: 79%
“…Although nurses reported a variety of nursing activities as not completed, the mean score showed that frequency of nursing care rationing was in the range from between 'never' and 'rarely'. The same range (less than rarely) of rationed nursing care frequency has also been found in several Polish studies (Jarosz et al, 2022;Kołtuniuk et al, 2021;Piotrowska et al, 2022;Witczak et al, 2022) or in Slovak study (Kalánková et al, 2022).…”
Section: Discussionsupporting
confidence: 79%
“…Studies were published between 2020 and 2023; however, nine of them completed the data collection in 2020 (e.g., [ 52 ]), 10 in 2021 (e.g., [ 47 ]), two between 2020 and 2021 [ 37 , 50 ], one in 2022 [ 55 ], two between 2019 and 2020 [ 35 , 54 ], and one between 2019 and 2021 [ 38 ]. Participants were mainly nurses, and their sample size ranged from 130 [ 42 ] to 672 [ 34 ] in 21 studies; in others, participants were generally identified as “care workers”, ranging from 374 [ 22 ] to 2,700 [ 40 ], while those including nursing assistants and registered nurses together ranged from 43 [ 48 ] to 287 [ 54 ] participants. The MISSCARE Survey tool was the most used (= 14, e.g., [ 44 ]), followed by BERNCA (= 1, [ 46 ]), Revised BERNCA (BERNCA-R) (= 2, [ 51 , 52 ]), BERNCA-NH (= 2, [ 22 , 40 ]), PIRNCA (= 4, e.g., [ 42 ]), ICU-ONC (= 1, [ 53 ]), and UNCS (= 1, [ 37 ]) (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The objective, standard criteria used to measure the condition were not assessable in any of the qualified studies, since the condition was considered the COVID-19 disease. At the overall level, all except six studies [ 25 , 34 , 42 , 43 , 46 , 55 ] documented the occurrence of and reasons for UNC activities.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, care rationing may be influenced by factors related to a given nurse, such as her skills, knowledge and attitudes [ 14 ]. The research also showed the influence of other factors closely related to the nurse on the rationing of care, e.g., professional burnout, fatigue, stress, job satisfaction, seniority, age, life satisfaction and life orientation [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%